Improving Understanding of Human Reproductive System Materials Using Padlet Application: Utilization of Digital Literacy in Science Learning - Kartina, Dewi (Journal of Learning Improvement and Lesson Study, 2022)
This article aims to improve understanding of human reproductive system material by using padlet applications. This is a digital literacy application for class IX students at the UNP Laboratory Development Junior High School. Padlet application is an online learning application that is synchronous online. In learning by using the padlet application, students and teachers can be present together in one learning platform. This research is a classroom action research (action research) with quantitative descriptive data processing techniques. The results of this study indicate an increase in student literacy, both data literacy and technological literacy by using padlet applications in science learning, especially material for the human reproductive system. This can be seen from the increase in learning outcomes from the first meeting to the third meeting